2020
DOI: 10.1186/s12876-020-01565-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound with fine needle aspiration is useful in pancreatic cysts smaller than 3 cm

Abstract: Background In current guidelines, endoscopic ultrasound with fine-needle aspiration (EUS-FNA) is recommended in pancreatic cystic lesions (PCLs) with worrisome features (size ≥ 3 cm, mural nodule, or Wirsung dilation). Objective To evaluate the diagnostic ability and assess the accuracy of EUS-FNA in PCLs smaller than 3 cm. Methods Retrospective study of PCLs < 3 cm (2007–2016) undergoing EUS-FNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…As shown in Figure 1, our initial query revealed 370 studies, being narrowed to 47 after careful selection of the abstracts, with 21 making the final cut for data extraction 14–34 . From these 21 papers, overall diagnostic accuracy data concerning only FNA or FNB were found in 13 and 14 studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1, our initial query revealed 370 studies, being narrowed to 47 after careful selection of the abstracts, with 21 making the final cut for data extraction 14–34 . From these 21 papers, overall diagnostic accuracy data concerning only FNA or FNB were found in 13 and 14 studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Endoscopic ultrasound (EUS) and EUS-guided the needle biopsy are useful in the management and diagnosis of pancreatic solid [ 19 ] or cystic lesions [ 20 22 ]. Li et al [ 23 ] reported that EUS with or without fine-needle aspiration had better performance in diagnosing pancreatic cystic neoplasms (PCNs) than CT or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The 2017 revised Fukuoka guidelines proposed using a cyst size greater than 3 cm as a worrisome feature to recommend performing EUS-FNA 2 . The 2015 American Gastroenterological Association guidelines proposed cyst size greater than 3 cm as one of 3 high-risk features, along with dilation of the main pancreatic duct and the presence of a mass or nodule, which should prompt an EUS-FNA, but only if 2 of these features are present simultaneously 33,34 . Thus, measuring telomere length using EUS-FNA samples in the presence of cysts greater than 3 cm may be of value.…”
Section: Discussionmentioning
confidence: 99%